Observations respecting Articles collected in the Outer Hebrides, and now presented to the Museum - Thomas, F W L (Proceedings of the Society of Antiquaries of Scotland, 1862)
Captain Thomas discusses some of the stone finds, ruins and folklore found in the Outer Hebrides. Many of the finds were discovered on the island of Taransay, near Harris.